Effects of feed composition, protein denaturation and storage of milk serum protein/lactose powders on lactosylation. (27th June 2020) - Andersson, Ida‐Marie; Bergenståhl, Björn; Alexander, Marcela; Paulsson, Marie; Glantz, Maria
Summary: During whey powder production, the feed is subjected to several heat treatments which can cause lactosylation of proteins. In this study, lactosylation of whey proteins was evaluated in spray‐dried powders before and after storage by varying the native protein fraction as well as the serum protein/lactose ratio in the powders. The lactosylation of native α‐lactalbumin and β‐lactoglobulin in the powders before storage was not affected to a large extent by the protein denaturation or if the feed had been heat treated in a high or low lactose environment. After storage (relative humidity of 23.5%, 30 °C, 25 days), the kinetic of lactosylation tended to increase with increasing native protein fraction and bulk protein content in the powders. An explanation could be that proteins dissolved in the lactose glassy structure might have a lower reactivity, while proteins present in the protein glassy structure with dissolved lactose may display higher lactosylation reactivity. Abstract : (a) Segregation of protein and lactose in a spray‐dried serum protein/lactose (% w / w ) powder particle. (b) Rate of lactosylation in powder samples as a function of protein/lactose ratio (% w / w, dry matter) during storage (RH 23.5%, 30 °C, 25 days).